2020
DOI: 10.47552/ijam.v11i2.1488
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and HPTLC study of Padina tetrastromatica (Hauck)

Abstract: The marine ecology is diverse with innumerable types of natural substances, both of plant and animal origin. Padina tetrastromatica (PT) (Hauck) is a brown algae belonging to the order Dictyotales, found in coastal region. The objective of present investigation was to evaluate phytochemical profile of extracts of PT. The air dried plant material was defatted and extracted successively with solvents of increasing polarity. Incumbent study was performed with standard qualitative phytochemical tests and HPTLC fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…Besides these, all components showed positive results in the methanolic extract of both seaweeds. Our present finding coincides with the findings of other authors; who also found several phytochemicals in case of altered solvents from brown seaweed P. tetrastromatica 20 , 33 . But in the case of G. tenuistipitata there has been no prior research on preliminary phytochemical screening was found in the literature.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Besides these, all components showed positive results in the methanolic extract of both seaweeds. Our present finding coincides with the findings of other authors; who also found several phytochemicals in case of altered solvents from brown seaweed P. tetrastromatica 20 , 33 . But in the case of G. tenuistipitata there has been no prior research on preliminary phytochemical screening was found in the literature.…”
Section: Discussionsupporting
confidence: 94%
“…The maximum significant application of seaweed is found in food industries, cosmetic industries, an industry of phycocolloid or hydrocolloid, biofuel production, wastewater treatment, pharmaceutical industry and fertilizer 18 , 19 . In general, seaweed contains different secondary metabolites, for example, tannins, saponins, phenols, and flavonoids in varying concentration 16 , 20 . In addition, seaweed has a wide range of bioactive compounds that have antibacterial, anti-Alzheimer’s, anti-inflammatory, antifungal, anti-hyperglycemic, anti-aging activities, and preferable antioxidant properties 21 – 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides these, all components showed positive results in the methanolic extract of both seaweeds. Our present nding coincide with the ndings of other authors; who also found several phytochemicals in case of altered solvents from brown seaweed P. tetrastromatica 20,33,34 . But in the case of G. tenuistipitata there has been no prior research on preliminary phytochemical screening was found in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…The maximum signi cant application of seaweed is found in food industries, cosmetic industries, an industry of phycocolloid or hydrocolloid, biofuel production, wastewater treatment, pharmaceutical industry and fertilizer 18,19 . In general, seaweed contains different secondary metabolites, for example, tannins, saponins, phenols, and avonoids in varying concentration 16,20 . In addition, seaweed has a wide range of bioactive compounds that have antibacterial, anti-in ammatory, antifungal, anti-aging activities, and preferable antioxidant properties 21,22 .…”
Section: Introductionmentioning
confidence: 99%